(untitled) (Salud, Arte y Cuidado, 2017)
Mitral stenosis is the obstruction of the left ventricular inlet tract by a generally rheumatic mitral valve pathology. The most frequent symptoms are dyspnea on exertion, which can sometimes progress to acute pulmonary edema, and palpitations. Hemoptysis, systemic embolisms, thoracic pain, and signs and symptoms of right failure may also be observed. Medical treatment is aimed at reducing symptoms and avoiding the impact of increased left atrial pressure on the pulmonary circulation; while surgical treatment should be considered in those patients with a disabling symptomatology or when the valvular area is less than or equal to 1.5 cm2. This paper presents the case of a 42-year-old female with a diagnosis of severe mitral stenosis associated with atrial fibrillation. The clinical status, the evolution, the findings of ECG and ECO-2D are examined. The pertinent considerations are made to the medical and surgical management, based on the criteria of the patient studied.